Analysis of Intrasession Repeatability of Ocular Aberrometric Measurements and Validation of Keratometry Provided by a New Integrated System in Mild to Moderate Keratoconus. Issue 9 (September 2019) - Piñero, David P.; Soto-Negro, Roberto; Ruiz-Fortes, Pedro; Pérez-Cambrodí, Rafael J.; Fukumitsu, Hideki
Abstract : Purpose: To evaluate the intrasession repeatability and validity of corneal curvature measurements provided by a new multifunctional device and to assess the intrasession repeatability of its ocular aberrometric measures. Methods: This prospective study comprises 37 mild to moderate keratoconus eyes of 37 patients. In all cases, 3 repeated measures of corneal topography and ocular aberrometry were performed with the iDesign 2 system (iD2; Johnson & Johnson Vision Care Inc, Jacksonville, FL) and one keratometric measurement was performed with the intraocular lens-(IOL) Master 500 (Carl Zeiss Meditec Inc, Dublin, CA) and Sirius (CSO) (SIR) systems. Results: The within-subject SD (Sw ) was <0.50 D for all iD2 keratometric measurements, with intraclass correlation coefficient (ICC) >0.980. Sw and ICC for the keratometric axis were 2.60 degrees and 0.992, respectively. Concerning aberrations, all Sw values for high-order Zernike terms were ⩽0.11 μm (ICC > 0.900), and all Sw values for refraction data were <0.75 D (ICC > 0.95), except for J45 . No statistically significant differences were found between the devices in any keratometric parameter evaluated ( P ≥ 0.222), but the limits of agreement between the devices were clinically relevant. The magnitude of K readings and astigmatism correlated significantly with the difference in these parameters between iD2 and SIR (0.432 ⩽ r ⩽ 0.489, P ⩽ 0.041). Conclusions: The iD2 system provides consistent measures of keratometry and ocular aberrometry in eyes with mild to moderate keratoconus. Keratometric data obtained with this system in these eyes cannot be considered as interchangeable with data provided by intraocular lens-Master 500 and SIR.